ANALISIS KEPUASAN KONSUMEN SARI BUAH BELIMBING MANIS (Arverrhoa carambola L) (STUDI KASUS DI UD CEMARA SARI KELURAHAN KARANGSARI KECAMATAN SUKOREJO KOTA BLITAR) - Safiq, Fauzan Al; Fatmawati, Erlin Widya (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
This study aims to determine the attributes of starfruit juice "Cemara Sari" which isconsidered important by consumers as well as to find out the level of customersatisfaction and map of crabs from starfruit juice "Cemara Sari". Research has beencarried out around star fruits agrotourism in Sukorejo Subdistrict, KarangsariSubdistrict, Blitar City, which began in February to March 2018. The research wasconducted by distributing questionnaires and interviews with the respondents. The dataobtained were tested using validity and reliability tests to determine the feasibility of thevariables. used in the questionnaire, in addition to knowing the level of customersatisfaction using the Customer Satisfaction Index (CSI) and to find out the mapquadrant attribute starfruit juice "Cemara Sari" using the Importance PeformanceAnalisys (IPA). The results showed that the variables in the questionnaire feasible to usewith r table of 0.196 and the results of the validity shows the lowest value is 0.448 andreliability (alpha) of 0.763. The results of the Customer Satisfaction Index (CSI) countshow a value of 69.79% and the Importance Peformance Analisys (IPA) addressQuadrant 1 in the contents of the variable smell and price, Kudran 2 in the contents ofthe taste variable, shelf life, packaging ability to protect the product and practicality ofpackaging, 3 In the contents of the texture, product color and attractiveness of thevariable, quadrant 4 is filled with the packaging color variable.